2016
DOI: 10.1080/15578771.2016.1226214
|View full text |Cite
|
Sign up to set email alerts
|

Use of Concept Maps to Illustrate Barriers to Construction Industry Inter-Organizational Communication: a Comparative View from Students and Professionals

Abstract: Because of the fragmented nature of construction industry inter-organizational communication, construction industry stakeholders must rely on information exchanges in order to produce new information and directives for the process. This communication process does not always happen smoothly due to possible barriers during the information flow. The purpose of this study is to understand these potential information flow barriers and to use concept maps to engage students in discussions about communication within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In particular, it is believed that communication is poorly performed in the AEC industry due to its fragmented nature (El Debs et al. , 2018), and consequently, the abundance of many difficult-to-understand project management concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, it is believed that communication is poorly performed in the AEC industry due to its fragmented nature (El Debs et al. , 2018), and consequently, the abundance of many difficult-to-understand project management concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shaurette (2014) highlights "resistance to change, time constraints" and "constraints when working across geographic boundaries" as challenges faced by universities when adding international components to the curriculum. Throughout the literature there is growing acknowledgement that changes in higher education are needed to promote global competencies and international experiences (El Debs, Brunese, & Shaurette, 2018). Global experiences for students can be fulfilled through many different international education and collaborative involvements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the importance of universities increasing the global competencies of students, many universities have not implemented strategies to expose the students to these areas because of significant barriers. Some of the challenges noted in the literature include resistance to change, time constraints, inflexible or incompatible reward systems, constraints created when working across geographic boundaries, limits to the use of active learning, limitations and continual changes in instructional technology, a diversity of views on and application of assessment, as well as limited international accreditation (El Debs et al, 2018).…”
Section: Barriers Associated With International Experiencesmentioning
confidence: 99%
“…El Debs et al (2016) on the importance of certifications to recent graduates found out that safety certifications (OSHA-10hr and OSHA-30hr) and sustainability certifications were ranked highest by industry people who were surveyed with a survey questionnaire. Barrows et al (2020) focused on the value of certifications in seeking employment where it showed that Project Management Professional (PMP) certification was most valued in senior project management levels followed by LEED AP.…”
Section: Certification In the Construction Industrymentioning
confidence: 99%